2019
DOI: 10.1136/vetreco-2019-000363
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit welfare: determining priority welfare issues for pet rabbits using a modified Delphi method

Abstract: BackgroundRabbits are the third most popular pet in the UK, but little research into their welfare needs has been conducted.MethodsA modified Delphi method was used to generate expert consensus on the most important welfare issues for rabbits in the UK. The study involved 11 experts, recruited from a range of disciplines. The experts generated an initial broad list of welfare issues via an online discussion board. Two rounds of online surveys were conducted to prioritise these issues. The final round was a wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 26 publications
0
45
0
1
Order By: Relevance
“…By comparing the outcomes from our data with those of other studies that have attempted similar types of assessments, we have found that there are common welfare concerns that are raised frequently with different groups, which lends greater weight to arguments that these are important issues for horse welfare. In particular, lack of owner knowledge, or application of knowledge to the management of horses, is an important welfare concern, which has also been seen in other species [21,51]. In addition, many of the other issues that have been highlighted may also stem from poor owner knowledge or the application of traditional or culturally mediated methods of managing or using horses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the outcomes from our data with those of other studies that have attempted similar types of assessments, we have found that there are common welfare concerns that are raised frequently with different groups, which lends greater weight to arguments that these are important issues for horse welfare. In particular, lack of owner knowledge, or application of knowledge to the management of horses, is an important welfare concern, which has also been seen in other species [21,51]. In addition, many of the other issues that have been highlighted may also stem from poor owner knowledge or the application of traditional or culturally mediated methods of managing or using horses.…”
Section: Discussionmentioning
confidence: 99%
“…The study formed part of a larger study to identify and prioritise welfare issues for a range of different species. Detailed methods were as previously described [21] and are given in brief here.…”
Section: Methodsmentioning
confidence: 99%
“…Pet rabbits are the third most popular pet in the western world [ 1 ], however with an increasing interest in their welfare from within the veterinary profession and the welfare science community, widespread welfare deficits have become apparent [ 1 , 2 , 3 , 4 , 5 , 6 ]. The British Veterinary Association (BVA) noted with consternation that 78% of UK vets believe pet rabbits’ welfare needs were not being met, reporting rabbits being housed inappropriately or alone and within an inappropriate environment [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both Rooney et al [ 7 ] and Mullan and Main [ 4 ] state that this inappropriate housing, without conspecifics, and often an inappropriate diet, would limit the behavioral repertoire and welfare of pet rabbits [ 4 , 7 ]. This welfare deficit due to potential husbandry failings within our pet rabbit population could lead to welfare compromise, a shortened lifespan, and painful medical problems such as dental disease [ 3 , 4 , 5 ]. Welch et al [ 8 ] carried out a large survey of 2890 rabbit owners (focused in the USA and Canada, but also covering some areas outside of North America), which focused on their knowledge of rabbit husbandry and their rabbits’ neutered status.…”
Section: Introductionmentioning
confidence: 99%
“…All research generated from this study was approved by the University of Edinburgh's Human Ethics Review Committee (HERC). The full description of the methods can be found in Rioja-Lang et al (13). The results presented here are part of a larger study that identified priority welfare issues for a number of managed animal species in the UK.…”
Section: Methodsmentioning
confidence: 99%